Wear Characteristics of 22MnB5 Boron Steel under Friction Micro Pin-on-Disks Test - Rashid, Mohd Fairuz; Abu Bakar, Hadzley; Adam, Abdul Aziz; Ali, Mohd Basri; Abu Bakar, Faizal (Journal of Sustainable Manufacturing in Transportation, 2021)
22MnB5 Boron Steel can be considered as emerged material for high strength and low weight application. This material potentially used in abrasive condition such as cutting tool or brake pad where high friction resistance applies. In this study, the wear characteristics of 22MnB5 was investigated under the frictional tests via micro pin-on-disk. 22MnB5 Boron Steel was prepared the form of round shape within the size of 2.6 mm thickness and 12 mm diameter by using laser cutting. 4 different samples were tested namely blank (sample A), self-hardening heat treatment (sample B), 60 HRC hot stamped (sample C) and 70 HRC hot stamped (sample D). The results show that Coefficient of Friction (COF) increased as the hardness of 22MnB5 decreased. Low COF of 0.2114 recorded for sample D with 70 HRC hardness. The COF increased to 0.24, 0.29 and 0.3 when sample C (60 HRC), sample B (52 HRC) and sample A (45.5 HRC) applied respectively. For pin-on disc test, worn area decreased as the hardness increased. 22MnB5 that prepared with the highest hardness of 70 HRC presented smallest wear area of 700 µm x 2400 µm. It is followed by 800 µm x 2400 µm, 1000 µm x 2400 µm, 1600 µm x 2800 µm, when sample C, B and A were scratched. Observation on the worn surface revealed delamination of 22MnB5 surface in the form of fragmented flaking debris